Correlation of Certain Alterations in Metabolic Activity with Alkaloid Production by Submerged Claviceps - Řeháček, Z. (1971)
Alkaloid biosynthesis in Claviceps paspali MG-6 was favored by unbalanced growth. A positive correlation between the rate of protein turnover and alkaloid formation was noted. The pattern of the orthophosphate content in the mycelium resembled that in the ripening sclerotia of the parasitic strains. Alkaloids were revealed as potentially effective in energy metabolism. Reduced adenosine triphosphate (ATP) utilization and an increase in the ATP pool were found to be favorable for alkaloid production. Acetyl-coenzyme A carboxylase activity and the level of cell lipids were directly related to the intensity of alkaloid biosynthesis. An inverse relationship was observed between the activities of the tricarboxylic acid and glycoxylate cycles and the rate of alkaloid formation.